High-Diluted-Biomedicines Turmeric Extract (TE) act as Preventive Policy- Developer-Potential-21st-Century-Pandemic COVID 19 Vaccines: Achieved Community-Communication-Medicine-Science-Applications-Public-Health-Ecology-Green-Technology-Innovations-Econom - Subhas Chandra Datta (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Introduction: Recently the COVID-19 Coronavirus-Disease-2019 caused by reinfection of the numerous new-mutant-coronavirus long-COVID-19-variant SARS-CoV-2, not only effects on global health, education, clinical research, economy, prolonged-neurological-damage, and total change of human civilization, but also its effects on some organs and tissues in Children causing the 'Multisystem-Inflammatory-Syndrome (MIS-C)' also, and the sixteen-months-pandemic have punctuated humanity's timeline for hundreds of years, sowing panic, millions of infections (188) and killing 4-millions. Though the middle-and upper-classes now enjoying the vaccination, the minority, and low-income households, are really suffering. Still, the pandemic prevails, and the main objectives of the research are to find out suitable cost-effective community-biomedicines or universal vaccines by using high-diluted-form of turmeric extract with the help of local students Non-Governmental-Organization (NGO), and doctors. Methods: In the 11-slam-area, the community-biomedicine of high-diluted-form, Turmeric Extract (TE) or turmeric MT, made from the turmeric-rhizome, Curcuma longa L., is mixed @10-20 drops (1-2mg) /cup (100ml-150ml) of moderately-hot germ-free-drinking-water, administered orally every-day in the early morning (with an empty-stomach) once/day for thirty-days before illness-onset as a preventive measure, with no need to ethical consideration for the permissible doses and safety concerns, OR may be applied after the symptom-onset against present coronavirus infections as a vaccine, where COVID-19 patients in hospitalized, and also the dose could also be increased looking on the intensity of diseases, and age, just in case of treatment suggested by the doctors, and the young-local-students NGO, the "Burdwan-Green-Haunter-and-Students'-Goal", take initiative for COVID-protocol, social-awareness- and treatment-camp with doctors. Results: The current preventive-treatment measures have shown that community-biomedicines of high-diluted-TE are more potent in preventing-pathogens by increasing-immunity against COVID-19 with the carcinogenic-free and 'Multisystem-Inflammatory-Syndrome (MIS-C)'-free results in the 11-slam treated-area than another-control-area of Purba Bardhaman, and the NGOs are an active-helper in all respect. Conclusions: The easily-available, easily-suppliable, easily-applicable, side-effects-free, non-toxic, cost-effective, eco-friendly, easily-preparable, and the 'MIS-C' free high-diluted-potential-community-biomedicine, Turmeric Extract, maybe act as preventive-policy-developer-potential-21st-century-pandemic COVID 19 vaccine by achieving community-medicine-clinical-research-public-health-ecology-green-socio-economy-welfare-science-innovations-technology-communication-applications-issues-advancements. In new normal, it'd be the foremost important vaccines by applying the community-biomedicines of ultra-high-diluted-TE against day-to-day new virulent-coronavirus pandemics, and another multidisciplinary-health-disease suffering from COVID-19 improving community-immunity-or-herd-immunity also, and NGO act as potential-'Social-Vaccines' again, using biotechnology, biological researchers, biomedical-study-processes, and the final goal of future developing-potential-treatments and cures.